2014
DOI: 10.12980/apjtb.4.2014c529
|View full text |Cite
|
Sign up to set email alerts
|

High–frequency in vitro plantlet regeneration from apical bud as a novel explant of Carum copticum L.

Abstract: In this study, a simple and reliable regeneration and acclimatization protocol for Carum copticum has been presented. This protocol can be found very advantageous for a variety of purposes, including mass multiplication of Carum species, medicinal plant breeding studies and transgenic plant production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…6a, b). The variation in proliferation, shoot and root regeneration response might be due to the influence of growth regulators and hormones on growing and developing callus (Salehi et al 2014), genotypic and phenotypic characters of the mother plant (Benderradji et al 2012). Due to the time necessity for whole plant regeneration, many authors (Ho and Vasil 1983; Ahloowalia and Maretzki 1983) did not mention clearly the process of plant regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…6a, b). The variation in proliferation, shoot and root regeneration response might be due to the influence of growth regulators and hormones on growing and developing callus (Salehi et al 2014), genotypic and phenotypic characters of the mother plant (Benderradji et al 2012). Due to the time necessity for whole plant regeneration, many authors (Ho and Vasil 1983; Ahloowalia and Maretzki 1983) did not mention clearly the process of plant regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…e.g. plant regeneration from callus of T. ammi (Jasrai et al 1992, Sehgal andAbbas 1994), callus induction and regeneration from apical bud of Carum copticum L. (Salehi et al 2014), direct shoot micropropagation system in T. ammi by using seed as explants (Koca and Aasim 2015), direct somatic embryogenesis from cotyledon and cotyledonary node explants in T. ammi (Purohit and Kothari 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The seeds were washed thoroughly under running tap water for 30 min. The soaked seeds were treated with 70% ethyl alcohol for 1 min and 0.5% (v/v) sodium hypochlorite for 10 min and then rinsed three times with sterile distilled water (Salehi et al 2014). The surface sterilized seeds were cultured on MS medium and incubated at 26 ± 2°C in darkness for germination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…tissue culture technique to ensure its restoration. Tissue culture methods offer highly efficient tools for germplasm conservation and mass multiplication of many threatened plant species (Salehi et al 2014;Ozel et al 2015). Sreedevi et al (2013) and Thangavel et al (2014a) have previously reported successful organogenesis from Plectranthus barbatus using leaf explants.…”
Section: Introductionmentioning
confidence: 99%